A heuristic evaluation checklist for mobile shopping applications - Uzoma, Ihediohamma Raphael (2022)
Studies on issues related to mobile shopping applications are numerous, however, there is inadequacy in implementing the heuristic evaluation approach to identifying and documenting definite kinds of issues as far as their classifications for mobile shopping applications. Recent studies have shown that there is a deficiency of proper evaluation methods and suitable heuristics and subheuristics needed in recognizing mobile-specific usability issues since existing checklists are either web-centered or developed for general mobile applications such as social media mobile applications and utility mobile applications, and not for mobile shopping applications. These existing checklists are incapable of identifying usability issues of mobile shopping applications; hence, this study aims to address these issues by developing a heuristic evaluation checklist for mobile shopping applications. The strategy employed in the evaluation comprises four phases: identifying problems and objectives, heuristic identification, heuristic evaluation checklist development, and heuristic checklist evaluation. Twelve domain experts verified the proposed heuristic evaluation checklist and data collected was analysed using the Fuzzy Delphi Method. The study successfully identified suitable heuristics and subheuristics that made up the proposed heuristic evaluation checklist. Subsequently, a heuristic evaluation was conducted by six domain experts comprising usability experts, software and mobile application developers, as well as mobile shopping application designers, and the results confirm the effectiveness of the proposed heuristic evaluation checklist in identifying significant usability issues in Shopee mobile shopping applications. Through the heuristic evaluation checklist, usability experts and analysts can direct a dynamically exact evaluation of online shopping applications. In the same method, software and mobile application developers as well as mobile shopping designers can logically design a usable interface following a set of usability standards that will meet users' satisfaction.